Personalized and Precision Medicine in Asthma and Eosinophilic Esophagitis: The Role of T2 Target Therapy - Diego Bagnasco; Edoardo Vincenzo Savarino; Mona-Rita Yacoub; Fulvio Braido; Maria Giulia Candeliere; Edoardo Giannini; Giovanni Passalacqua; Elisa Marabotto (Pharmaceutics, 2023)
The role of type 2 inflammation has been progressively associated with many diseases, including severe asthma, atopic dermatitis, nasal polyposis, eosinophilic granulomatosis with polyangiitis, and, recently, eosinophilic esophagitis. Despite this, the association between asthma and esophagitis is still poorly known, and this is probably because of the low prevalence of each disease and the even lower association between them. Nonetheless, observations in clinical trials and, subsequently, in real life, have allowed researchers to observe how drugs acting on type 2 inflammation, initially developed and marketed for severe asthma, could be effective also in treating eosinophilic esophagitis. For this reason, clinical trials specifically designed for the use of drugs targeted to type 2 inflammation were also developed for eosinophilic esophagitis. The results of clinical trials are presently promising and envisage the use of biologicals that are also likely to be employed in the field of gastroenterology in the near future. This review focuses on the use of biologicals for type 2 inflammation in cases of combined severe asthma and eosinophilic esophagitis.